A review of climatic and vegetation surveys in urban environment with laser scanning: a literature-based analysis - Szabó, Zsuzsanna; Schlosser, Aletta; Túri, Zoltán; Szabó, Szilárd (Geographica Pannonica, 2020)
Laser scanning is a promising relatively new technology of land surveying and has different contributions to research areas and practical applications. We performed a review based on query terms in the Scopus database. We determined the number of papers where the laser scanning was the technique of the survey and refined the results with the aerial (ALS) and terrestrial (TLS) laser scanning methods, and the urban and vegetation searching terms. Results showed that geosciences had a 30-40% ratio within the scientific papers using LiDAR. TLS had larger relevance related to ALS considering the total number of research papers, urban application and vegetation analysis in urban environment. We analysed the current status of the technology and discussed the underlying possible causes.